2010
DOI: 10.1007/s10433-010-0167-z
|View full text |Cite
|
Sign up to set email alerts
|

What drives retirement income worries in Europe? A multilevel analysis

Abstract: Nations in Europe have been developing rapidly since the formation of the European Union (EU), not only socially and demographically, but economically as well. One question a number of countries will face during this period of structural transition will be how (and how well) they are able to support their citizens in old age. A related question involves whether individuals worry about their financial future in retirement, and the extent to which they take active steps to save in order to ensure an adequate sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 35 publications
6
35
0
1
Order By: Relevance
“…In countries where most families live in rented houses, people will have to pay rent until the end of their lives, which leaves them less room for savings. Moreover, the saving behavior is related to the feeling of being uncertain about one's future, and Hershey's et al (2010) analysis clearly shows that there are differences across nations in the degree of retirement worries, as well as differences in the propensity to save for the future. While low levels of worry can be observed in Scandinavian countries and the Netherlands, Europeans from Eastern Europe reported high levels of worry.…”
Section: Savingsmentioning
confidence: 98%
“…In countries where most families live in rented houses, people will have to pay rent until the end of their lives, which leaves them less room for savings. Moreover, the saving behavior is related to the feeling of being uncertain about one's future, and Hershey's et al (2010) analysis clearly shows that there are differences across nations in the degree of retirement worries, as well as differences in the propensity to save for the future. While low levels of worry can be observed in Scandinavian countries and the Netherlands, Europeans from Eastern Europe reported high levels of worry.…”
Section: Savingsmentioning
confidence: 98%
“…It is suggested that women are in higher need to postpone their retirement for financial reasons (Hofäcker et al, 2019) and they may even be more likely to do so if they worry about their financial security after retirement. To analyse whether (anticipated) pension income has any psychological effects, we therefore investigate worries about the financial situation after retirement, although Swedes seem to report less worries about their retirement income in comparison to other European countries (Hershey et al, 2010). This was partly related to generally low income inequalities in Sweden since a high Gini coefficient was related to higher worries.…”
Section: The Swedish Pension System and Preconditions For Pension Benmentioning
confidence: 99%
“…Therefore, despite losing one of the most important roles in life, one can set new goals and develop non-professional passions. The change of social role from employee to retiree is a natural process, but such a big change in life may lead to negative psychological effects [16][17][18][19]. Changes in different aspects of life due to the retirement threshold have been studied in many countries.…”
Section: Introductionmentioning
confidence: 99%